Thermo-resettable cross-linked polymers for reusable/removable adhesives. Issue 47 (15th November 2018) - Das, Sandip; Samitsu, Sadaki; Nakamura, Yasuyuki; Yamauchi, Yoshihiro; Payra, Debabrata; Kato, Kazuaki; Naito, Masanobu
Abstract : Reusable and removable adhesives have been synthesized using dynamic Diels–Alder chemistry with high lap shear strength, good reusability and easy removability. Abstract : Resettable thermosetting adhesive systems have been explored with the help of a thermo-reversible Diels–Alder (DA) reaction between a furan-bearing random copolymer and bismaleimide as a dynamic bond cross-linkage. The obtained adhesive materials exhibited good lap shear strength in the cross-linked state of up to ∼8 MPa. In addition, the bonding/debonding state of the adhesives could be reset by an appropriate choice of thermal treatment.